Protective Effects of Rapamycin on Trabecular Meshwork Cells in Glucocorticoid-Induced Glaucoma Mice - Zhu, Xiaolu; Wu, Shengyu; Zeng, Wen; Chen, Xiaomin; Zheng, Tian; Ren, Jiangbo; Ke, Min (Frontiers in Pharmacology, 2020)
Glucocorticoid-induced Glaucoma (GIG) is a chronic optic neuropathy caused by systemic or topical glucocorticoid treatment, which could eventually lead to permanent vision loss. To investigate the protective effects of rapamycin (RAP) on the trabecular cells during the development of GIG in mice, the effects of RAP on IOP, trabecular ultrastructure and retinal ganglion cells (RGCs) were examined in C57BL/6J female mice treated with dexamethasone acetate (Dex-Ace). The expression of α-actin in trabecular tissue was detected by immunofluorescence, and the autophagic activity of trabecular cells and the expression of GIG-related myocilin and α-actin were detected by immunoblotting. Our results indicated that Dex-Ace significantly increased IOP at the end of the third week (p < 0.05), while RAP treatment neutralized this elevation of IOP by Dex-Ace. The number of RGCs in Dex-Ace significantly decreased RGC numbers (p < 0.05), while synchronous RAP treatment kept the number comparable to control. The outer sheath of elastic fibers became thicker and denser, and the mitochondria of lesions increased in Dex-Ace-treated groups at 4 weeks, while no significant change was observed in the RAP-treated trabecular tissues. Dex-Ace induced α-actin, Beclin-1 and LC3-II/LC-I ratio, and lowered p62. However, synchronous RAP treatment neutralized these effects. Our studies suggested that RAP protected trabecular meshwork cells from damages of glucocorticoid treatment.